2015
DOI: 10.1016/j.jacc.2015.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable Vascular Scaffolds Versus Metallic Stents in Patients With Coronary Artery Disease

Abstract: In the present multicenter randomized trial, BVS was noninferior to CoCr-EES for the primary endpoint of in-segment LL at 1 year. (A Clinical Evaluation of Absorb Bioresorbable Vascular Scaffold [Absorb BVS] System in Chinese Population-ABSORB CHINA Randomized Controlled Trial [RCT]; NCT01923740).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
121
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(137 citation statements)
references
References 14 publications
6
121
0
2
Order By: Relevance
“…Thereafter, several randomized clinical trials compared it to the bestin-class everolimus-eluting stent (EES), namely Xience (Abbott Vascular, Santa Clara, USA). These trials confirmed the preliminary results from the prospective registries by showing comparable clinical outcome between the BVS and the EES at short term follow up (2,3). With the extended follow up and real world implantation of the scaffold, we started to face a new entity, which is "BVS failure".…”
Section: Introductionsupporting
confidence: 66%
“…Thereafter, several randomized clinical trials compared it to the bestin-class everolimus-eluting stent (EES), namely Xience (Abbott Vascular, Santa Clara, USA). These trials confirmed the preliminary results from the prospective registries by showing comparable clinical outcome between the BVS and the EES at short term follow up (2,3). With the extended follow up and real world implantation of the scaffold, we started to face a new entity, which is "BVS failure".…”
Section: Introductionsupporting
confidence: 66%
“…This resulted into a smaller sample size than ABSORB 3 (N=480), but nonusable conclusions at the clinical level. The difference in 1-year in-segment late lumen loss was 0.06 mm (0.19±0.38 mm in the BVS group and 0.13±0.38 mm in the EES group), and the upper bound of the confidence interval was just 1 mm below the non-inferiority threshold (7). ABSORB Japan used a wide non-inferiority margin for the difference in 1-year TLF (8.6%), based on an agreement with the Japanese Pharmaceutical and Medical Device Agency, which resulted in a small sample size (N=400).…”
mentioning
confidence: 84%
“…After a first evaluation of titles and abstracts 38 records were screened and 26 of these were excluded because they did not meet the inclusion criteria and 6 because they were duplicate ( Figure 1). A total of seven studies were included in the meta-analysis (18)(19)(20)(21)(22)(23)(24), one of which was added after the publication in March 2017 (AIDA trial) (25). We also decided to use the data at two years, recently published in clinicaltrial.org for ABSORB III trial (26).…”
Section: Search Strategymentioning
confidence: 99%